Music and communication in music psychology. (November 2014) - Cross, Ian
There is a general consensus that music is both universal and communicative, and musical dialogue is a key element in much music-therapeutic practice. However, the idea that music is a communicative medium has, to date, received little attention within the cognitive sciences, and the limited amount of research that addresses how and what music communicates has resulted in findings that appear to be of limited relevance to music therapy. This article will draw on ethnomusicological evidence and an understanding of communication derived from the study of speech to sketch a framework within which to situate and understand music as communicative practice. It will outline some key features of music as an interactive participatory medium – including entrainment and floating intentionality – that can help underpin an understanding of music as communicative, and that may help guide experimental approaches in the cognitive science of music to shed light on the processes involved in musical communication and on the consequences of engagement in communication through music for interacting individuals. It will suggest that the development of such approaches may enable the cognitive sciences to provide a more comprehensive, predictive understanding of music in interaction that could be of direct benefit to music therapy.